2003
DOI: 10.1007/s11661-003-0160-7
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of thermosolutal convective instabilities in Ni-based single-crystal superalloys: Carbide precipitation and rayleigh numbers

Abstract: The influence of carbide precipitation on grain-defect formation during unidirectional solidification of experimental single-crystal Ni-based superalloys has been assessed over a wide range of compositions with large variations in Re, W, and Ta. In all instances, carbon additions of up to 0.15 wt pct were determined to be statistically significant with respect to stabilizing against the formation of grain defects, such as freckle chains, during solidification. Assessment of the segregation behavior of the cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 38 publications
4
47
0
1
Order By: Relevance
“…Alternatively, the kinematic viscosity and thermal diffusivity are maintained as constants and are, as a product, considered equal to the value 5 9 10 -12 m 4 /s 2 . [11,13,14] Because this consistent approximation is used by various investigators, no discrepancies between the results of this and other investigations are introduced by its use. However, it is unlikely that kinematic viscosity, thermal diffusivity, or their product remain constant over the entire liquidus to solidus temperature range in most alloys, including those presented in this study.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Alternatively, the kinematic viscosity and thermal diffusivity are maintained as constants and are, as a product, considered equal to the value 5 9 10 -12 m 4 /s 2 . [11,13,14] Because this consistent approximation is used by various investigators, no discrepancies between the results of this and other investigations are introduced by its use. However, it is unlikely that kinematic viscosity, thermal diffusivity, or their product remain constant over the entire liquidus to solidus temperature range in most alloys, including those presented in this study.…”
Section: Discussionmentioning
confidence: 88%
“…The Rayleigh numbers calculated with experimentally determined permeabilities are higher than those determined with conventional permeability approximations. [11,14] Additionally, it has been shown that permeability scales inversely with interfacial surface area independent of the degree of flow path tortuosity. As a result, the dimensionless liquid ratio f…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 However, the enrichment of Ta in the interdendritic melt can be reduced by carbon additions because of the formation of TaC; 19-21 the ␥/␥Ј eutectic content is therefore reduced. 19 CMSX-4 has about 70% higher Ta + Al contents than IN792. In particular, CMSX-4 is carbon-free alloy, whereas IN792 is a carbon-containing alloy.…”
Section: A Comparison Of the Castability Of Cmsx-4 In792 And Cm247mentioning
confidence: 99%